TRUTH AND RECONCILIATION COMMISSIONS AND LEGAL ORDER - Bianca Elena RADU (Challenges of the Knowledge Society, 2023)
The transition periods from abusive regimes to democratic ones put into action, among others, mechanisms such as Truth and Reconciliation Commissions, non-judiciary instruments of transitional justice, through which generalised abuses committed in the recent past of a country are investigated. Legal order is considered an indispensable foundation in establishing a state and in maintaining and, respectively, consolidating democracy. Starting from the theoretical-explanatory model of law philosophy that places the human being at the centre of lawmakers’ preoccupations, the present paper intends to show, at least at the theoretical level, the connection between the founding/functioning of Truth and Reconciliation Commissions and legal order. In the first part of the paper I will define legal order and the insoluble connection between it and judicial order. In the second part, I will explain the peculiarities of Truth and Reconciliation Commissions so as to show, in the last part, how the principles and their manner of functioning constitute the premises necessary for the configuration of the new rule of law, in societies marked by transition periods, as a result of experiencing systematic and generalised abuses. The paper has a heuristic value by showing, through the issue set forward, the concept of law as the art of good and equity – jus est are boni et aequi – promoted by Celsius.